Integrated Serum Pharmacochemistry and Network Pharmacology Approach to Explore the Effective Components and Potential Mechanisms of Menispermi Rhizoma Against Myocardial Ischemia - Wei, Jinxia; Yu, Yingying; Zhang, Yue; Li, Lingzhi; Li, Xia; Shao, Jia; Li, Yubo (Frontiers in Chemistry, 2022)
Background: Myocardial ischemia is the main cause of human death in the world. Menispermi Rhizoma is a kind of traditional Chinese medicine which has a variety of pharmacological activities in many diseases including myocardial ischemia. Purpose: Serum pharmacochemistry and network pharmacology were used to explore the material basis and mechanism of Menispermi Rhizoma in the treatment of myocardial ischemia. Methods: The blood components of Menispermi Rhizoma were analyzed by ultra performance liquid chromatography/quadrupole time-of-flight tandem mass spectrometry (UPLC/Q-TOF-MS) technology, and the key components, targets, pathways and interrelated information were obtained by network pharmacology. On this basis, the effective components of Menispermi Rhizoma in the treatment of myocardial ischemia were screened by MTT, and the results of network pharmacology and the cardioprotective effect of Menispermi Rhizoma were verified by Western blot and molecular docking. Results: 25 compounds of Menispermi Rhizoma, including acutumine, daurisoline, dauricoside and 6-O-demethylmenisporphine were detected. Network pharmacology revealed 81 major targets of Menispermi Rhizoma against myocardial ischemia mainly by regulating key pathways of the PI3K-Akt and MAPK pathways. And in vitro validation in oxygen glucose deprivation (OGD) model of H9c2 cells found that the contents of lactate dehydrogenase (LDH), creatine kinase (CK) and malondialdehyde (MDA) were significantly decreased by the four alkaloids of Menispermi Rhizoma, on the contrary, the activities of superoxide dismutase (SOD) and glutathione (GSH) were significantly increased. Western blot results showed that four alkaloids up-regulated the expression ratio of Bcl-2/Bax and down regulated the expression levels of Cyt-C and cleaved caspase 3, which further supported the anti cardiomyocyte apoptosis and anti oxidative stress effect of Menispermi Rhizoma. Molecular docking confirmed that four compounds are capable of binding with AKT1, MAPK1, EGFR, CASP3 and MAPK8 proteins, further confirming the inhibitory effect of Menispermi Rhizoma on the PI3K-Akt and MAPK pathways. Conclusion: It is proved that the cardioprotective effect of Menispermi Rhizoma and its mechanism depend on multi-component, multi-target, multi-pathway, especially Menispermi Rhizoma may play an anti-apoptotic role by regulating PI3K-Akt and MAPK pathways.